Implementasi Pendidikan Multikultural pada Progam Kurikuler sebagai Sarana Membangun Karakter Bangsa di Sekolah Dasar - Lisa Retnasari; Yayuk Hidayah (Universitas Negeri Medan, 2019)
This research aims to explain the implementation process of multicultural education as the media to build the character of the nation through the curricular program in primary school. The method used is the qualitative descriptive. The subject of this research includes the headmaster of the school, educator and the students by using purposive sampling. The instrument to gather information includes observation, documentation, and interview. The knowledge regarding the multicultural education includes respect diversities, understand, and accept diversities, either gender, religion, tribe, ethnic, culture, beliefs, economic ability, social condition, besides that the ability of the students to accept their friends who have academic differences either higher academic ability of lower academic ability, how the students can accept achievements in learning, the condition of the students either ABK that has disabilities or mental illness as an act to build the character of the nation. The multicultural learning program is done through: curriculum based on multicultural, intra-curricular program through morning carpet and day carpet, and co-curricular program (assembly, mini trip, resource person, and multiage).